Effects of dexmedetomidine on Apgar score, NBNA score of newborns and maternal hemodynamic in cesarean section - LI Wulan, WANG Jun, XU Tao, ZHOU Nina, TANG Guoqiang (Zhongguo linchuang yanjiu)
Objective To investigate the effects of dexmedetomidine on the safety of newborns, and maternal hemodynamic parameters and nerve block of cesarean section. Methods The clinical data of 117 cases of cesarean section delivery admitted to the Zigong First People’s Hospital from July 2021 to October 2022 were retrospectively analyzed. The women were divided into two groups based on whether dexmedetomidine was given before anesthesia, 52 cases who were not given dexmedetomidine were divided into control group, and 65 cases who were given dexmedetomidine before anesthesia were divided into observation group. The two groups were compared with the newborn’s Apgar score, the Neonatal Behavioral Neurological Assessment (NBNA), maternal hemodynamic indicators, sensory block, motor block, and maternal complications. Results There was no significant difference in the Apgar score and the NBNA score at 2 and 4 days between the two groups of newborns (P＞0.05). Compared with 1 minute before drug infusion (T1), the mean arterial pressure in both groups was significantly reduced at 5 minutes after drug infusion (T2), 10 minutes before the end of surgery (T3), and at the time of fetal delivery (T4), and the mean arterial pressure of T2 to T4 in the observation group were higher than those of the control group. Heart rate of T2 to T4 in the observation group was significantly higher than that of T1, but the heart rate of T2 to T4 in the observation group was lower than that of the control group (P＜0.05), and there was no statistical difference in saturation of peripheral oxygen (SpO2) between the two groups at all time points (P＞0.05). The time of onset of sensory block and motion block of observation group were shorter than those of control group. The duration of sensory block and motion block of observation group were longer than those of control group (P＜0.05). The total incidence of maternal complications in the observation group was lower than that in the control group (4.62% vs 17.31%, χ2=5.056, P=0.025). Conclusion Dexmedetomidine before anesthesia can improve the stability of hemodynamics parameters, shorten the onset time of sensory and motor block, extend the duration of sensory and motor block, reduce the incidence of maternal complications, and has no significant impact on the neonatal Apgar score and NBNA score.